2017
DOI: 10.1002/brb3.649
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of Brief‐Balance Evaluation Systems Test (Brief‐BESTest) in evaluating balance performance in individuals with chronic stroke

Abstract: ObjectiveTo examine the psychometric properties of the Brief‐Balance Evaluation Systems Test (Brief‐BESTest) in individuals with chronic stroke.Materials and MethodsThis was an observational study with repeated measurements involving 50 participants with chronic stroke [mean (SD) age: 59.2 (7.3) years]. Each participant with stroke was evaluated with the Brief‐BESTest, Berg balance scale (BBS), Postural Assessment Scale for Stroke Patients (PASS), Fugl‐Meyer Motor Assessment (FMA), Chedoke‐McMaster Stroke Asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…The S-BESTest, the Mini-BESTest, the Brief-BESTest, and the BESTest demonstrated good internal responsiveness (large SRM), suggesting all 4 versions of the BESTest were sensitive in detecting the effectiveness of rehabilitation in subacute stroke. Results regarding acceptable SRM were in accordance with previous studies on psychometric properties of the BESTest in patients with subacute and community-dwelling stroke (13,15,17). However, when considering the external responsiveness using the BBS as the reference, our study showed that only the S-BESTest and the original BESTest demonstrated higher accuracy in identifying the patients with subacute stroke who had balance improvement with the mean MCID of 6 and 16 points, respectively.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The S-BESTest, the Mini-BESTest, the Brief-BESTest, and the BESTest demonstrated good internal responsiveness (large SRM), suggesting all 4 versions of the BESTest were sensitive in detecting the effectiveness of rehabilitation in subacute stroke. Results regarding acceptable SRM were in accordance with previous studies on psychometric properties of the BESTest in patients with subacute and community-dwelling stroke (13,15,17). However, when considering the external responsiveness using the BBS as the reference, our study showed that only the S-BESTest and the original BESTest demonstrated higher accuracy in identifying the patients with subacute stroke who had balance improvement with the mean MCID of 6 and 16 points, respectively.…”
Section: Discussionsupporting
confidence: 90%
“…However, when there is the need for reducing assessment time or the need to identify patients with balance improvement, the S-BESTest is the most appropriate choice for balance assessment in patients with subacute stroke. In contrast, the Brief-BESTest and the Mini-BESTest may be more suitable for assessing postural control in patients with chronic stroke, as previous studies found no floor effect in patients with chronic stroke using the Brief-BESTest and the Mini-BESTest (15,17). The floor effect of the Brief-BESTest and Mini-BESTest in subacute stage may be due to the fact that these 2 scales contain items that are more difficult for patients with subacute stroke to perform.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The CMSA leg and foot scale each comprise of levels 1–7, the lower the level the greater the degree of neurological deficit. Evaluation measures included the 10 m walk test (10MWT) [ 33 ], 6 min walk test (6minWT) [ 34 ], and the Brief Balance Evaluation Systems Test (Brief-BESTest) [ 35 ]. These descriptive and evaluation measures were used to characterize the PWS participant group (refer to Table 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…[ 7 ] Balance dysfunction after stroke is related to poorer mobility, and ability to perform activities of daily living, and falls. [ 8 ] Patients with hemiplegia after stroke have weakened or lost control of motor function on the affected side of the trunk. The patients’ standing balance and walking ability are limited due to the damage of balance center in the nervous system.…”
Section: Introductionmentioning
confidence: 99%